Characterization of Green Pigment from Sauropus androgynus Shoot Cultures - Oeke Yunita; Devi Veronica Wijayanto; Aulia Dwi Hapsari; Muji Lestari Wahyu Wilang Sari; Alfian Hendra Krisnawan (Fakultas Farmasi, Universitas Surabaya, 2021)
The dark green leaves of Sauropus androgynus (Euphorbiaceae) have various nutritive values and are commonly used for human consumption as food, medicine, and natural dye substance in South-east Asia. Shoot cultures of this plant were established by adding various concentrations of kinetin (Kn) and benzyl adenine (BA) using nodal explants. The best results were recorded when Kn 0.1 mg/L was used with BA 1 mg/L (BA1Kn0.1). Spectrophotometric analysis showed two peaks of green pigment in shoot cultures, A pigment (λmax = 663.6 - 663.8 nm, absorbance 0.1111) and B pigment (λmax= 611.3 - 613.9 nm, absorbance 0.0390). Thin Layer Chromatography (TLC) analysis showed two green spots (Rf Y = 0.31 and Rf Z = 0.25) of shoot cultures on medium supplemented with BA1Kn0.1 for 10 days. Pigment profiles of shoot culltures were similar to their corresponding mother plants. Random Amplified Polymorphic DNA (RAPD) was used as a preliminary technique to evaluate the genetic similarity of the shoot cultures and their corresponding mother plants. It showed four similar DNA banding patterns to their leaves, ranging from 271-765 bp.